Avanços na criopreservação do sêmen ovino I: diluidores e crioprotetores - Bittencourt, Rodrigo Freitas (2013)
The effectiveness of using frozen sheep semen in artificial insemination programs requires the development of extenders and freezing protocols that will increase pregnancy rate of inseminated females. This work aimed to survey the main extenders, additives and external and internal cryoprotectants that have been employed to improve the maintenance levels of sperm parameters after the freezing-thawing process. Better rates of post-thawing sheep sperm viability may be obtained with changes in the freezing extender composition, whether by the adjustment of its components or by introducing additives that inhibit the occurrence of sperm changes during the cryopreservation process. Thus, the possible changes proposed must take into consideration the intrinsic characteristics of ram semen and the individual variability among animals. It is important to emphasize that the sperm cryopreservation effectiveness requires that all process steps are conducted in an integrated manner, to maximize the fertility rate of frozen ram semen.